Flexible Electronics: Extremely Flexible Transparent Conducting Electrodes for Organic Devices (Adv. Energy Mater. 1/2014). Issue 1 (January 2014) - Jung, Sunghoon; Lee, Sunghun; Song, Myungkwan; Kim, Do‐Geun; You, Dae Sung; Kim, Jong‐Kuk; Kim, Chang Su; Kim, Tae‐Min; Kim, Kwon‐Hyeon; Kim, Jang‐Joo; Kang, Jae‐Wook
<x xml:space="preserve">Abstract</x> In article 1300474, Jang‐Joo Kim, Jae‐Wook Kang, and co‐workers report the development of extremely flexible transparent conducting electrodes for organic device applications. The electrodes are fabricated using a combination of metal‐embedding architecture into a plastic substrate and ultrathin transparent electrodes and they exhibit high conductivity and extreme flexibility. These electrodes are used to fabricate flexible organic solar cells and organic light‐emitting diodes that exhibit performances similar or superior to those of devices fabricated on glass substrates. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>